The psychology of Buddhism in conflict studies - de Silva, Padmasiri (Switzerland : Switzerland, 2017)
This book provides an interdisciplinary discussion of conflict studies, drawing on perspectives from psychology and Buddhist studies.
Includes bibliographical reference and index.
Keywords: Buddhism -- Psychology; Conflict management -- Buddhism. -- Religious aspects; Conflict (Psychology).